(untitled) (Western Journal of Medical and Biomedical Sciences, 2023)
A 69-year-old diabetic woman presented to the medical emergency following a 2-week history of fever and left-sided flank pain, urinary frequency, nocturia and urge-incontinence. No polyuria, and no polydipsia.On examination, she was lethargic, pale, febrile (T038.60C), dehydrated, and marked left-sided renal angle tenderness. Dipstick urinalysis revealed pyuria (3+), ketones (2+), and positive nitrite. Urine microscopy showed numerous white blood cells. Both urine and blood culture yielded significant growth of Escherichia coli (extended-spectrum beta-lactamase producer). Abdominopelvic computed tomography and intravenous urogram (CT-IVU) scan showed a mal-rotated and inferiorlysited left kidney with multiple, rounded hypo-dense lesions with rim enhancement within its parenchyma and rightsided moderate hydronephrosis. A diagnosis of xanthogranulomatous pyelonephritis and diabetic ketoacidosis in an elderly woman with congenital anomaly of the left kidney was made. She was treated with intravenous antibiotics, and counselled for left-sided nephrectomy, but declined surgery. She was followed up in the clinic and had three readmissions before she died four months after the diagnosis.